The “Tempered Radical” Revolution: Multifocal Strategies of Religious-Zionist Feminism in Israel - Zion-Waldoks, Tanya (Religions, 2021)
Agunah activism, a flagship struggle of Religious-Zionist feminism, links gender politics, Jewish-Orthodox politics, and national Israeli politics. This qualitative study focuses on agunah activists’ strategies and conceptions of change, highlighting the complex ways religious women radically transform conservative contexts, complicated by intersections of religion, gender, and state. It examines dynamic boundary-work and how activists deploy the inner workings of “the Halakhic framework” to shift creatively between social positioning, ideological or cultural positioning, and a political positioning to create “change from within”. My case study troubles the premise that religion and feminism are antithetical, and that distinct identities or set social locations predetermine social movements’ frames or actions. I expand upon the term “tempered radicals” which challenges reformist/revolutionary and conservative/radical binaries. “Tempered radical” strategies are two-pronged: a tempered mode of modulation and moderation to rock the boat without falling out (avoid the red lines, find “the right way”) and a radical mode of stirring the sea and creating horizons (arrive there, one way or another). Dynamically holding both modes together, through a “multifocal lens”—the world-as-it-is and the world-as-it-should-be—enables their strategic maneuverings. They remain “within” while radically transforming individuals, communities, Jewish law, Orthodox society and the Israeli public sphere. This study demonstrates how religious and gendered structures are at once constitutive and mutable.